Why dry areas should invest massively in innovation to ensure food security - Rijsberman, Frank (CGIAR Consortium, 2014)
Keynote speech by Frank Rijsberman at the Global Forum for Innovations in Agriculture (GFIA), 3 February 2014, Abu Dhabi